(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
Bread is also an important source of minerals. It contains potassium, phosphorus, magnesium, and, in somewhat smaller quantities, sodium, calcium, chlorine, and others. Lower-grade breads contain more minerals. Currently, the issue of high-quality bakery products is becoming increasingly pressing. This article presents the results of laboratory studies, comparative evaluations, and quality assessments of bakery products. Two types of bread were examined , and an organoleptic assessment of bread quality was conducted, along with studies of physicochemical parameters (crumb moisture, crumb acidity, and crumb porosity). These expert assessment results indicate that the products sold are manufactured in accordance with GOST requirements, with compliance with all stages of the technological process.